Congestive heart failure in older adults diagnosed with follicular lymphoma: A population‐based study. Issue 21 (10th October 2018) - Kenzik, Kelly M.; Mehta, Amitkumar; Richman, Joshua S.; Kilgore, Meredith; Bhatia, Smita
Abstract : Background: To the authors' knowledge, there is limited information regarding the long‐term risk of congestive heart failure (CHF) among patients with follicular lymphoma, a prevalent non‐Hodgkin lymphoma diagnosis among those aged >65 years, especially within the context of therapeutic exposures and preexisting comorbidities. Methods: Using Surveillance, Epidemiology, and End Results–Medicare data from 1999 through 2013, the authors identified 6109 patients with follicular lymphoma who were diagnosed at age ≥66 years between January 1, 2000 and December 31, 2011, and a frequency‐matched Medicare noncancer sample. Subdistribution hazards models assessed risks associated with new‐onset CHF through December 31, 2013. Propensity score–matched models examined CHF risk in patients receiving anthracyclines when compared with matched noncancer controls. Results: When compared with matched controls, patients with follicular lymphoma receiving anthracyclines at ages 66 to 75 years had a 1.7‐fold (95% confidence interval, 1.4‐fold to 2.1‐fold) higher risk of new‐onset CHF; patients diagnosed at age >75 years did not differ from noncancer controls with regard to CHF risk. Preexisting hypertension was associated with a 1.7‐fold and 1.35‐fold, respectively, increased hazard of CHF for each age group, independent of anthracycline exposure. Preexisting diabetes was associated with 1.5‐fold increased hazard of CHF only in those patients aged 66 to 75 years. Patients with new‐onset CHF had a 18% lower 10‐year survival compared with those without CHF. Conclusions: Patients with follicular lymphoma who were exposed to anthracyclines between the ages of 66 years and 75 years were found to be at an increased risk of new‐onset CHF; preexisting hypertension and diabetes appeared to increase this risk. The findings of the current study support and inform the risk‐based follow‐up of vulnerable populations. Abstract : Compared with an age‐matched and comorbidity‐matched control population, anthracycline‐exposed patients with follicular lymphoma who were diagnosed between the ages of 66 years and 75 years are at a greater risk of new‐onset congestive heart failure. The risk of new‐onset congestive heart failure among those diagnosed at age >75 years does not appear to be significantly increased.